Drug instrumentalization - Müller, Christian P. (Behavioural Brain Research, 2020)
Psychoactive drugs with addiction potential are widely used by people of virtually all cultures in a non-addictive way. In order to understand this behaviour, its population penetrance, and its persistence, drug instrumentalization was suggested as a driving force for this consumption. Drug instrumentalization theory holds that psychoactive drugs are consumed in a very systematic way in order to make other, non-drug-related behaviours more efficient. Here, we review the evolutionary origin of this behaviour and its psychological mechanisms and explore the neurobiological and neuropharmacological mechanisms underlying them. Instrumentalization goals are discussed, for which an environmentally selective and mental state-dependent consumption of psychoactive drugs can be learned and maintained in a non-addictive way. A small percentage of people who regularly instrumentalize psychoactive drugs make a transition to addiction, which often starts with qualitative and quantitative changes in the instrumentalization goals. As such, addiction is proposed to develop from previously established long-term drug instrumentalization. Thus, preventing and treating drug addiction in an individualized medicine approach may essentially require understanding and supporting personal instrumentalization goals.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Drug abuse; Drug addiction; Drug instrumentalization; Drug use; Instrumentalization goals